Characterization of Metamaterials for the Fabrication of Printed Antennas - Benchaoui Fatima Zahraa; Bouzouad Mouloud (UNIVERSITY AMAR TELIDJI LAGHOUAT-FACULTY OF TECHNOLOGY-DEPARTEMENT OF ELECTRONICS, 2025)
This thesis presents the design, simulation, and fabrication of a reconfigurable metamaterial supercell intended for dynamic control of printed antenna operating frequencies. The core innovation involves a 4x4 supercell composed of two types of 3x3 mm² unit cells: a connected cross-type (A) exhibiting a near-zero refractive index, and a disconnected cross-type (B) with a refractive index slightly greater than unity. A novel reconfigurable switching mechanism allows for arbitrary spatial arrangement and proportion of these unit cell types, enabling dynamic control over the supercell's electromagnetic response. The unit cell period (3 mm) ensures subwavelength operation at 2.4 GHz. Detailed electromagnetic simulations characterized various configurations, demonstrating the ability to control the resonant frequency of an integrated patch antenna by varying the percentage of disconnected unit cells (6.25%, 12.5%, 18.75%, 25%) and their spatial distribution. This work establishes a robust method for real-time frequency tuning, offering significant advancements for adaptive and flexible smart antenna systems in modern wireless telecommunications.
Option : Networks and telecommunications